PREVALENCE OF UNDER-NUTRITION AND ANEMIA AMONG UNDER FIVE RURAL CHILDREN OF SOUTH KARNATAKA, INDIA - Nanjunda, Nanjunda (Journal of Health and Allied Sciences NU, 2014)
Infant and under five mortality rates are reliable indicators of health status of the children of any country. Despite accelerated growth, the prevalence of hunger, poor health status, under nutrition and mortality in rural part of the country are still persisting in India. While under nutrition among children is pervasive; child mortality is rather high in rural parts of India. The current study conducted in two remote villages of Hassan and Kodagu districts of South Karnataka-India. Study conducted on ( Boys 160, Girls 140) preschool children, selected through stratified sampling design technique. Through this study stunting in 75.0 %, wasting in 81.7% and underweight in 87.6% of both Boys and Girls of pre-school children were found. In case of Anemia, 48% of Girls and 56% of Boys were severely affected; while 47 % of Girls and 41% of the Boys were modestly affected and 10% of the Boys and 28% Girls observed mildly affected. It is also found that clinical sign of Anemia among 62% of the studied children. Next, 21% children found Vitamin A deficiency and 22% children found vitamin B complex deficiency. The Study also found that only 67% children put on breastfeeding within Three hours after the birth in the studied village. It is also noted that income poverty, bad personal habits, changing health seeking behavior, cultural practices regarding delivery, child rearing and breastfeeding also plays a vital role in case of mortality problem where Government and NGO (Non- Gov. Organizations) should focus on these issues immediately.
Keywords: Mortality; Nutrition; Health; Rural; Children